Preparation method and application of high-stability and high-conductivity PEDOT (poly (3, 4-ethylenedioxythiophene)) nano dispersion

By adjusting the mass ratio of EDOT and dispersant during the PEDOT preparation process and terminating the oxidative polymerization reaction in advance, the problem of difficult to achieve both high conductivity and high dispersion stability of PEDOT is solved, and efficient and stable PEDOT nanodispersions are prepared, which improves the performance and preparation efficiency of organic photovoltaic cells.

CN119955073AActive Publication Date: 2025-05-09WUHAN INST OF TECH
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202510126741.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-27
Publication Date
2025-05-09
Estimated Expiration
2045-01-27

AI Technical Summary

Technical Problem

In the prior art, it is difficult to have both high conductivity and high dispersion stability of PEDOT, which limits its application in electronic devices.

Method used

By setting the mass ratio of EDOT and dispersant to be 1:x, x is 2.5 to 25, and the oxidation polymerization reaction is terminated in advance when the PEDOT yield and the weight ratio of the dispersant reaches 1:x, a high stability and high conductivity PEDOT nanodispersion was prepared.

Benefits of technology

While ensuring the stability of PEDOT dispersion, it can improve the quality of PEDOT, significantly improve the efficiency of organic photovoltaic cells, and greatly shorten the preparation time of conductive polymers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure HDA0005260091360000011
    Figure HDA0005260091360000011
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a high-stability and high-conductivity PEDOT nano dispersion, and relates to the technical field of photoelectric materials. The PEDOT nano dispersion comprises PEDOT and a dispersing agent, the mass ratio of PEDOT to the dispersing agent is 1: x, and x is 2.5-25; the preparation method comprises the following steps: 1) adding an EDOT monomer and a dispersing agent into water, then adding acid to adjust the pH value, then adding an oxidizing agent, and stirring at room temperature to react; wherein the mass ratio of the EDOT monomer to the dispersing agent is 1: y, y < lt >; x; and 2) monitoring an oxidative polymerization reaction, removing unreacted raw materials through membrane separation when the weight ratio of the PEDOT yield to the dispersant reaches 1: x, and terminating the reaction to obtain the high-stability and high-conductivity PEDOT nano dispersion. The obtained PEDOT nano dispersion has high stability and high conductivity at the same time, has low zeta potential and high in-plane / external conductivity, and can significantly improve the efficiency of an organic photovoltaic cell when being used as a hole transport material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of optoelectronic materials, and specifically relates to a preparation method and application of a high-stability and high-conductivity PEDOT nano-dispersion. Background Art

[0002] In 1990, Bayer AG of Germany invented polystyrene sulfonic acid doped poly (3,4-ethylenedioxythiophene) PEDOT:PSS conductive polymer (EP0440957; US5300575) nanodispersion, which has excellent film-forming, optical and electrical properties and is widely used in antistatic coatings, capacitors, light-emitting diodes, perovskite solar cells, thermoelectric materials, biosensors and other fields. In recent years, electronic devices have developed rapidly, and the electrical properties of classic PEDOT:PSS can no longer match the deeper energy level structure and higher carrier density of the new generation of organic semiconductor materials, which has gradually become a bottleneck problem restricting the development of electronic devices.

[0003] Conductive polymer nanodispersions are usually formed by fully oxidative polymerization and in-situ self-assembly of 3,4-ethylenedioxythiophene (EDOT) monomers in a dispersant (such as PSS) solution system. Researchers usually obtain highly conductive PEDOT nanodispersions by ① increasing the amount of oxidant, ② increasing the EDOT feed ratio, and ③ adjusting the dispersant structure. However, excessive use of oxidants will cause complex flocculation of oxidant cations and dispersant anions (Fe 3+ ----SO 3 2- )(Spectrochim.Acta A 2023,293,122445;Macromolecules 2022,55,450). Secondly, the increase in the proportion of PEDOT and the decrease in the proportion of dispersant will also greatly reduce the dispersion stability of PEDOT (J.Power Sources2017,358,29). In addition, the structural adjustment of the dispersant often comes at the expense of dispersion ability (Adv.EnergyMater.2022,12,2103892). This has created a situation in which high conductivity and high dispersion stability are mutually exclusive and difficult to achieve, which has seriously restricted the further development and application of PEDOT conductive polymers. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation method and application of a high-stability, high-conductivity PEDOT nanodispersion, so as to solve the problem in the prior art that high conductivity and high dispersion stability of PEDOT are mutually exclusive and difficult to achieve at the same time, and to help improve the performance of conductive polymers and organic photovoltaic cells.

[0005] In order to achieve the above purpose, the technical solutions adopted are as follows:

[0006] Provided is a method for preparing a high-stability, high-conductivity PEDOT nanodispersion, wherein the PEDOT nanodispersion comprises PEDOT and a dispersant, wherein the mass ratio of PEDOT to the dispersant is 1:x, and x is 2.5 to 25;

[0007] The preparation method specifically comprises the following steps:

[0008] 1) Add 3,4-ethylenedioxythiophene (EDOT) monomer and dispersant into water, then add acid to adjust pH, then add oxidant, and stir at room temperature for reaction; wherein the mass ratio of EDOT monomer to dispersant is 1:y,y <x;

[0009] 2) The oxidative polymerization reaction is monitored. When the weight ratio of PEDOT production to dispersant reaches 1:x, the unreacted raw materials are removed by membrane separation and the reaction is terminated to obtain a highly stable and highly conductive PEDOT nanodispersion.

[0010] According to the above scheme, in the step 1), the dispersant is one or more of lignin sulfonate, polystyrene sulfonate (PSS), polynaphthalene sulfonate, fluorocarbon sulfonate, polycarboxylate, and sodium dodecylbenzene sulfonate; preferably one or more of polystyrene sulfonate, polynaphthalene sulfonate, and fluorocarbon sulfonate.

[0011] According to the above scheme, in step 1), the mass ratio of the water to the total mass of the raw materials EDOT and the dispersant is (200-10):1, preferably (100-25):1.

[0012] According to the above scheme, in step 1), the acid is one or more of sulfuric acid, hydrochloric acid, phosphoric acid, and carboxylic acid, preferably hydrochloric acid.

[0013] According to the above scheme, in step 1), the concentration of the acid is 1 to 10 mol / L, preferably 2 to 3 mol / L.

[0014] According to the above scheme, in step 1), the acid regulates the pH of the solution to 1-2, preferably 1-1.5.

[0015] According to the above scheme, in the step 1), the oxidant is a binary composite oxidant of persulfate and iron salt, the persulfate is preferably ammonium persulfate, sodium persulfate or potassium persulfate, and the iron salt is preferably ferric chloride, ferric sulfate, ferrous chloride or ferrous sulfate; the molar ratio of the persulfate, iron salt and EDOT is (1.2-3):(0.01-0.5):1, preferably (1.2-2):(0.05-0.3):1.

[0016] According to the above scheme, in step 1), the stirring speed at room temperature is 500 to 1800 rpm, preferably 800 to 1500 rpm.

[0017] According to the above scheme, in step 1), y is 0.10x to 0.35x.

[0018] According to the above scheme, in step 2), the reaction progress is monitored in real time using UV-visible-near infrared spectroscopy. Preferably, the monitoring of the oxidative polymerization reaction is to track the characteristic absorption of PEDOT at 400-1300nm, preferably 600-1100nm.

[0019] UV-Vis-NIR spectroscopy was used in advance to determine the PEDOT characteristic absorption in the 400-1300nm range of the PEDOT nanodispersion with a mass ratio of PEDOT to dispersant of 1:x, and the corresponding absorbance data was obtained as a standard. During the actual reaction process, UV-Vis-NIR spectroscopy was used to monitor the reaction and track the PEDOT characteristic absorption in the 400-1300nm range. When the absorbance value increased to the same as the standard value, the mass ratio of the product PEDOT to the dispersant was also 1:x, and the reaction was stopped.

[0020] According to the above scheme, in the step 2), the oxidative polymerization reaction time is 10 to 120 minutes.

[0021] According to the above scheme, in the step 2), the membrane separation method is dialysis, the molecular weight cutoff is 1-20KDa, preferably 5-10KDa; the dialysis frequency is 5-30min / time, preferably 5-15min / time; the dialysis time is 3-10h, preferably 5-8h.

[0022] According to the above scheme, in step 2), during dialysis, a dichloromethane solution is used to extract the aqueous solution outside the dialysis bag to recover the remaining EDOT monomer.

[0023] A method for preparing a highly stable and highly conductive PEDOT nanodispersion obtained by the above preparation method is to use the nanodispersion as a hole transport material in preparing a hole transport layer of an organic photovoltaic cell.

[0024] According to the above scheme, the hole transport layer is prepared by spin coating of the PEDOT nanodispersion.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. The present invention provides a method for preparing a highly stable and highly conductive PEDOT nanodispersion. By setting the proportion of dispersant in the raw materials (EDOT and dispersant) to be less than the proportion of dispersant in the target product, and terminating the oxidative polymerization reaction in advance when the weight ratio of PEDOT output and dispersant reaches the expected ratio, the problem of generating low-quality PEDOT due to too low oxidant concentration in the late stage of the reaction is avoided, and high-quality PEDOT is ensured. On the premise of ensuring the dispersion stability of PEDOT (proportion of dispersant), the quality of PEDOT is improved, and the dilemma of high conductivity and high dispersion stability of PEDOT, which are difficult to obtain at the same time, is cleverly resolved. A PEDOT nanodispersion with low zeta potential and high conductivity is prepared, and its use as a hole transport material significantly improves the efficiency of organic photovoltaic cells.

[0027] 2. While ensuring high conductivity and high dispersion stability, the present invention also greatly reduces the production cycle of the conductive polymer, significantly shortening the preparation time of the conductive polymer from 8 to 200 hours to 10 to 120 minutes, significantly improving the effect and being extremely time-competitive.

[0028] 3. The method of the present invention is simple, efficient and widely applicable. It has great research and promotion value for developing high-performance conductive polymer nanodispersion products with independent intellectual property rights. It is expected to provide diversified choices for improving the performance of conductive polymers and promote the development of conductive polymers to a new level. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is the UV-visible-near infrared absorption spectra of the PEDOT:PSS dispersions in Comparative Examples 1 to 3 and Examples 1 to 3.

[0030] Figure 2 It is the S2p spectrum of the thin film X-ray photoelectron spectrum of the PEDOT:PSS samples in Comparative Examples 1 to 3 and Examples 1 to 3.

[0031] Figure 3 The current-voltage characteristic curves of the PM6:BTP-eC9 thin film organic photovoltaic cells of the PEDOT:PSS samples in Comparative Examples 1 to 3 and Examples 1 to 3.

[0032] Figure 4 1 is the current-voltage characteristic curve of the D18:L8BO thin film organic photovoltaic cell of the PEDOT:PSS sample in Comparative Example 1 and Example 1. DETAILED DESCRIPTION

[0033] The following specific embodiments further illustrate the technical solutions of the present invention, but the protection scope claimed by the present invention is not limited to the scope involved in the embodiments.

[0034] Comparative Example 1: The raw material EDOT:PSS-1:8 was fully reacted for 84 hours to prepare the product PEDOT:PSS-1:8.

[0035] 0.6 g (4.2 mmol) of 3,4-ethylenedioxythiophene monomer and 4.8 g of polystyrene sulfonate (PSS) dispersant were added to 340 ml of pure water; then, 3 M hydrochloric acid was added to adjust the pH value of the system to 1.5, and 1.437 g (6.3 mmol) of ammonium persulfate and 13.6 mg (0.084 mmol) of ferric chloride were added to the above system, and the reaction was stirred at room temperature at 800 rpm; during this period, UV-visible-near infrared spectroscopy was used to track the characteristic absorption of PEDOT in the range of 600-1100 nm. When the absorbance no longer increased, the reaction was completed, which took about 84 hours; then, the reaction solution was transferred to a dialysis bag with a molecular weight cutoff of 10 KDa and dialyzed for 5 days, during which the water was changed 20 times to obtain a pure PEDOT:PSS-1:8 nanodispersion.

[0036] Comparative Example 2: The raw material EDOT:PSS-1:10 was fully reacted for 96 hours to prepare the product PEDOT:PSS-1:10.

[0037] 0.6 g (4.2 mmol) of 3,4-ethylenedioxythiophene monomer and 6 g of PSS dispersant were added to 400 ml of pure water; then, 3 M hydrochloric acid was added to adjust the pH value of the system to 1.5, and 1.437 g (6.3 mmol) of ammonium persulfate and 13.6 mg (0.084 mmol) of ferric chloride were added to the above system, and the reaction was stirred at room temperature at 800 rpm; during this period, UV-visible-near infrared spectroscopy was used to track the characteristic absorption of PEDOT in the range of 600-1100 nm. When the absorbance no longer increased, the reaction was completed, which took about 96 hours; then, the reaction solution was transferred to a dialysis bag with a molecular weight cutoff of 10 KDa and dialyzed for 5 days, during which the water was changed 20 times to obtain a pure PEDOT:PSS-1:10 nanodispersion.

[0038] Comparative Example 3: The raw material EDOT:PSS-1:16 was fully reacted for 150 hours to prepare the product PEDOT:PSS-1:16.

[0039] 0.6 g (4.2 mmol) of 3,4-ethylenedioxythiophene monomer and 9.6 g of PSS dispersant were added to 580 ml of pure water; then, 3 M hydrochloric acid was added to adjust the pH value of the system to 1.5, and 1.437 g (6.3 mmol) of ammonium persulfate and 13.6 mg (0.084 mmol) of ferric chloride were added to the above system, and the reaction was stirred at room temperature at 800 rpm; during this period, UV-visible-near infrared spectroscopy was used to track the characteristic absorption of PEDOT in the range of 600-1100 nm. When the absorbance no longer increased, the reaction was completed, which took about 150 hours; then, after the reaction was completed, the reaction solution was transferred to a dialysis bag with a molecular weight cutoff of 10 KDa and dialyzed for 5 days, during which the water was changed 20 times to obtain a pure PEDOT:PSS-1:16 nanodispersion.

[0040] Example 1: The raw material EDOT:PSS-1:2.5, react for 60 minutes, and prepare the product PEDOT:PSS-1:8.

[0041] 0.6g (4.2mmol) 3,4-ethylenedioxythiophene monomer and 1.5g PSS dispersant were added to 170ml pure water; then, 3M hydrochloric acid was added to adjust the pH value of the system to 1.5, and 1.437g (6.3mmol) ammonium persulfate and 13.6mg (0.084mmol) ferric chloride were added to the above system, and the reaction was stirred at room temperature at 1200rpm; during this period, the characteristic absorption of PEDOT in the range of 600-1100nm was tracked by UV-visible-near infrared spectroscopy. When the absorbance increased to the same as that of the product in comparative example 1 (taking about 60min), the reaction solution was transferred to a dialysis bag with a molecular weight cutoff of 10KDa, and high-frequency dialysis (frequency of 10min / time, dialysis time of 5h) was performed to obtain a pure PEDOT:PSS-1:8 nanodispersion. During the dialysis, 500ml of dichloromethane solution was used to extract the aqueous solution outside the dialysis bag to recover the remaining EDOT monomer.

[0042] Example 2: The raw material EDOT:PSS-1:2.5, react for 45 minutes, and prepare the product PEDOT:PSS-1:10.

[0043] 0.6g (4.2mmol) 3,4-ethylenedioxythiophene monomer and 1.5g PSS dispersant were added to 170ml pure water; then, 3M hydrochloric acid was added to adjust the pH value of the system to 1.5, and 1.437g (6.3mmol) ammonium persulfate and 13.6mg (0.084mmol) ferric chloride were added to the above system; the reaction was stirred at room temperature at 1200rpm; during this period, the characteristic absorption of PEDOT in the range of 600-1100nm was tracked by UV-visible-near infrared spectroscopy. When the absorbance increased to the same as that of the product of comparative example 2 (taking about 45min), the reaction solution was transferred to a dialysis bag with a molecular weight cutoff of 10KDa, and high-frequency dialysis (frequency of 10min / time, dialysis time of 6h) was performed to obtain a pure PEDOT:PSS-1:10 nanodispersion. During the dialysis, 500ml of dichloromethane solution was used to extract the aqueous solution outside the dialysis bag to recover the remaining EDOT monomer.

[0044] Example 3: The raw material EDOT:PSS-1:2.5, react for 30 minutes, and prepare the product PEDOT:PSS-1:16.

[0045] 0.6g (4.2mmol) 3,4-ethylenedioxythiophene monomer and 1.5g PSS dispersant were added to 170ml pure water; then, 3M hydrochloric acid was added to adjust the pH value of the system to 1.5, and 1.437g (6.3mmol) ammonium persulfate and 13.6mg (0.084mmol) ferric chloride were added to the above system; the reaction was stirred at room temperature at 1200rpm; during this period, the characteristic absorption of PEDOT in the range of 600-1100nm was tracked by UV-visible-near infrared spectroscopy. When the absorbance increased to the same as that of the product of comparative example 3 (taking about 30min), the reaction solution was transferred to a dialysis bag with a molecular weight cutoff of 10KDa, and high-frequency dialysis (frequency of 10min / time, dialysis time of 7h) was performed to obtain a pure PEDOT:PSS-1:16 nanodispersion. During the dialysis, 500ml of dichloromethane solution was used to extract the aqueous solution outside the dialysis bag to recover the remaining EDOT monomer.

[0046] The following are the characterization and performance test results of the products obtained in the embodiments and comparative examples.

[0047] Figure 1The UV-visible-near infrared absorption spectra of the PEDOT:PSS dispersions in Comparative Examples 1 to 3 and Examples 1 to 3 are shown. The test instrument used is a UV-2500 UV spectrophotometer (Shimadzu, Japan). In the absorption spectrum, the UV absorption peak of 190-300nm is the characteristic absorption of PSS, and the broad peak of 600-1100nm is the characteristic absorption band of PEDOT. The characteristic absorptions in Comparative Examples 1 to 3 and Examples 1 to 3 overlap, respectively, proving that the ratios of PEDOT:PSS in Comparative Examples 1 to 3 and Examples 1 to 3 are completely consistent, that is, the ratios of PEDOT:PSS in Examples 1 to 3 are 1:8, 1:10, and 1:16, respectively.

[0048] Figure 2 The following are the S2p spectra of the thin film X-ray photoelectron spectra of the PEDOT:PSS samples in Comparative Examples 1 to 3 and Examples 1 to 3, and the test instrument used is the Xeuss 3.0Xenocs X-ray photoelectron spectrometer (Synop, France). In the S2p spectrum, the peaks around 169eV and 164eV are respectively attributed to the characteristic signals of PSS and PEDOT sulfur. The XPSPEAK software is used to divide the PEDOT characteristic peak around 164eV into neutral and oxidized PEDOT peaks, and then the proportions of oxidized PEDOT in Comparative Examples 1, 2, and 3 (i.e., doping degrees) are calculated to be 16.5%, 16.3%, and 13.8%, respectively, and the proportions of oxidized PEDOT in Examples 1, 2, and 3 (i.e., doping degrees) are 22.8%, 20.1%, and 20.2%, respectively. The above results show that the quality of PEDOT in Examples 1, 2, and 3 is better than that in Comparative Examples 1, 2, and 3, respectively. Higher PEDOT quality (i.e., doping degree) will give the PEDOT:PSS samples in Examples 1, 2, and 3 higher carrier density and stronger charge transfer performance.

[0049] Table 1 shows the zeta potential data of the PEDOT:PSS dispersions in Comparative Examples 1 to 3 and Examples 1 to 3, and the testing instrument used is Malvern Panalytical Laser Particle Sizer MS2000 (Malvern, UK). At the same content of dispersant PSS, the zeta potential values ​​of the PEDOT:PSS dispersions in Examples 1 to 3 are lower than those in Comparative Examples 1 to 3, respectively, indicating that the PEDOT prepared by this method has better dispersion stability, which is conducive to long-term storage and use.

[0050] Table 1. Zeta potential data of PEDOT:PSS dispersions in Comparative Examples 1 to 3 and Examples 1 to 3

[0051]

[0052] Table 2 shows the film surface (σ) of the PEDOT:PSS samples in Comparative Examples 1 to 3 and Examples 1 to 3.∥ ) and out-of-plane conductivity (σ ⊥ ) data, the thin film conductivity test method refers to Journal of Materials Chemistry A, 2022, 10, 23165 and Nature Energy, 2022, 7, 352. Under the same PEDOT:PSS ratio, the film in-plane conductivity of the PEDOT:PSS samples in Examples 1, 2, and 3 is 3.5 times, 5.4 times, and 42.8 times that of the PEDOT:PSS samples in Comparative Examples 1, 2, and 3, respectively, which proves the advantages of the present invention in obtaining high-conductivity PEDOT:PSS products. In addition, for the problem of out-of-plane conductivity in the field, the PEDOT:PSS conductive polymer is prepared by the method of the present invention, and an increase of 23% to 121% can be obtained, which further illustrates the advantages of the present invention in out-of-plane conductivity. Such excellent conductive properties not only make the PEDOT:PSS products in Examples 1, 2, and 3 ideal candidate materials for hole transport layer materials of organic photovoltaic cells, but also become more excellent precursor materials for “secondary doping post-processing”.

[0053] Table 2. Conductivity data of PEDOT:PSS samples in Comparative Examples 1 to 3 and Examples 1 to 3

[0054]

[0055] Figure 3The current-voltage characteristic curves of the PM6:BTP-eC9 thin-film organic photovoltaic cells of the PEDOT:PSS samples in Comparative Examples 1 to 3 and Examples 1 to 3 are shown. The cell structure is ITO / PEDOT:PSS / PM6:BTP-eC9 / PDINN / Ag, and the assembly and testing methods refer to Journal of Materials Chemistry A, 2022, 10, 23165. PEDOT:PSS is used as a standard hole transport material without any treatment, and the PM6:BTP-eC9 active layer additive is conventional 1,8-diiodooctane (DIO). The thin-film photovoltaic cell efficiencies of the PEDOT:PSS samples in Comparative Examples 1, 2, and 3 obtained from the current-voltage characteristic curves are 17.86%, 17.17%, and 14.57%, respectively, and the thin-film solar cell efficiencies of the PEDOT samples in Examples 1, 2, and 3 are 18.52%, 18.18%, and 17.51%, respectively. The efficiency of 18.52% is the highest efficiency of the binary heterojunction PM6:BTP-eC9 (additive DIO) standard solar cell system. Under the same PEDOT:PSS ratio, the thin-film solar cell efficiency of the PEDOT:PSS samples in Examples 1, 2, and 3 was increased by 3.4%, 5.88%, and 20.2% respectively compared with the comparative example, proving the advantages of the product of the present invention in assembling high-performance organic photovoltaic cells. In addition, the higher efficiency makes the PEDOT:PSS product of the present invention a more excellent precursor material for "secondary doping post-processing", providing new opportunities for breaking through the bottleneck of organic photovoltaic cell efficiency.

[0056] Figure 4 The current-voltage characteristic curves of the D18:L8BO thin film organic photovoltaic cells of the PEDOT:PSS samples in Comparative Example 1 and Example 1 are shown. The cell structure is ITO / PEDOT:PSS / D18:L8BO / PDINN / Ag, and the assembly and testing methods refer to the PM6:BTP-eC9 cell. PEDOT:PSS is used as a standard hole transport material without any treatment. The thin film photovoltaic cell efficiencies of the PEDOT:PSS samples in Comparative Example 1 and Example 1 are obtained from the current-voltage characteristic curves to be 18.98% and 20.04%, respectively. The efficiency of 20.04% is one of the highest efficiencies of a binary heterojunction standard solar cell system, further demonstrating the beneficial effects of the product of the present invention in promoting the development of organic photovoltaic cells.

[0057] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement methods and fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a high-stability and high-conductivity PEDOT nanodispersion, wherein the PEDOT nanodispersion comprises PEDOT and a dispersant, wherein the mass ratio of PEDOT to the dispersant is 1:x, and x is 2.5 to 25; It is characterized in that The preparation method specifically comprises the following steps: 1) Add 3,4-ethylenedioxythiophene monomer and dispersant into water, then add acid to adjust pH, then add oxidant, and stir at room temperature for reaction; wherein the mass ratio of 3,4-ethylenedioxythiophene monomer to dispersant is 1:y,y <x; 2) The oxidative polymerization reaction is monitored. When the weight ratio of PEDOT production to dispersant reaches 1:x, the unreacted raw materials are removed by membrane separation and the reaction is terminated to obtain a highly stable and highly conductive PEDOT nanodispersion.

2. The preparation method according to claim 1, characterized in that: In the step 1), the dispersant is one or more of lignin sulfonate, polystyrene sulfonate, polynaphthalene sulfonate, fluorocarbon sulfonate, polycarboxylate, and sodium dodecylbenzene sulfonate; the acid is one or more of sulfuric acid, hydrochloric acid, phosphoric acid, and carboxylic acid; and the oxidant is a binary composite oxidant of persulfate and iron salt.

3. The preparation method according to claim 2, characterized in that: The molar ratio of the persulfate, the iron salt and the EDOT is (1.2-3):(0.01-0.5):

1.

4. The preparation method according to claim 1, characterized in that: In the step 1), the mass ratio of the water to the total mass of EDOT and the dispersant is (200-10):

1.

5. The preparation method according to claim 1, characterized in that: In the step 1), the concentration of the acid is 1 to 10 mol / L.

6. The preparation method according to claim 1, characterized in that: In the step 1), the acid is used to adjust the pH of the solution to 1-2.

7. The preparation method according to claim 1, characterized in that: In the step 1), y is 0.10x to 0.35x.

8. The preparation method according to claim 1, characterized in that: In the step 2), the reaction progress is monitored in real time using UV-Vis-NIR spectroscopy.

9. The preparation method according to claim 1, characterized in that: In the step 2), the oxidative polymerization reaction time is 10 to 120 minutes.

10. Use of the high-stability and high-conductivity PEDOT nanodispersion prepared by the preparation method according to any one of claims 1 to 9 as a hole transport material in the preparation of a hole transport layer of an organic photovoltaic cell.

Citation Information

Patent Citations

  • New polythiophene dispersions, their preparation and their use

    EP0440957A2

  • Polythiophene dispersions, their production and their use

    US5300575A

  • Method for preparing flexible poly(3,4-ethylenedioxythiophene) composite conductive thin film

    CN101704958A

  • Dispersions comprising polythiophenes with defined content of thiophene monomer

    CN103180386A

  • Method for in-situ synthesis of PEDOT (poly(3,4-ethylenedioxythiophene)) / nano silver transparent conductive coating

    CN104861189A